(untitled) (Sains Humanika, 2015)
Discussion forum of e-learning is one of the tools which contain threads for a topic posted. Students discuss or solve the topic within a group. In the group activity, students behave like a leader or follower. Among the followers, there are possibilities of student who is isolated to exist. However, it is not easy to identify the isolated student just by seeing the posts of the discussion because the discussion forum of e-learning requires duration. This research analyses the pattern of isolated student’s interaction through phases, using the log analysis and the social network analysis to reveal the isolated student’s position. The study found isolated students in every phase and even though not interacting with other students, some of them are still accessing the content of discussion forum. This means that the student is still gaining knowledge in a passive manner. This finding assists the facilitator to be aware of the isolated students and encourage them for better participation in the discussion.